An Integrated Numerical Hydrodynamic Shallow Flow-Solute Transport Model for Urban Area - Alias N.A.; Mohd Sidek L. (Institute of Physics Publishing, 2023)
Fluid dynamics; Forecasting; Hydrodynamics; River pollution; Rivers; Solute transport; Urban transportation; Convection diffusion; Developed model; Early Warning System; Flood modeling; Numerical hydrodynamics; One-dimensional (1D) models; Solute transport model; Two Dimensional (2 D); Floods; accuracy assessment; early warning system; flood frequency; flow modeling; hazard management; hydrodynamics; hydrological modeling; numerical model; prediction; solute transport; urban area; urbanization; Malaysia